The loving push : how parents and professionals can help spectrum kids become successful adults - Grandin, Temple; Moore, Debra (Arlington, TX : Future Horizons, Inc., 2015)
Parents, teachers, therapists, and anyone who cares about a child or teen on the autism spectrum needs this essential roadmap to prepare our youth for being successful adults in today's world. Best-selling author, autism advocate, and animal science professor Dr. Temple Grandin joins psychologist and autism specialist Dr. Debra Moore in spelling out the steps you can take to restore your child's hope and motivation, and what you must avoid. Eight life stories are told by people on the autism spectrum, including chapters on subjects such as how to get kids off their computers, how to build on their strengths and get back to caring about their lives, and how to find a path to a successful, meaningful life.
Real stories, real successes : 8 inspiring profiles -- The three necessary components of your child's success -- How to break you child's bad habits : a necessary step so your child keeps moving forward -- Stretching your child just outside their comfort zone -- What to do when you kid doesn't seem to care or is chronically anxious -- Compulsive gaming and media recluses -- Teaching vital life skills needed for success -- Final thoughts.
Includes bibliographical references (page 199-208).
Keywords: Parents of autistic children; Autistic children -- Life skills guides; Autistic children -- Rehabilitation; Autism -- Popular works